Factors associated with HIV-1 resistance to integrase strand transfer inhibitors in Spain: Implications for dolutegravir-containing regimens - Gil, Horacio; Delgado, Elena; Benito, Sonia; Moreno-Lorenzo, María; Thomson, Michael M.; , the Spanish Group for the Study of Antiretroviral Drug Resistance (Frontiers in Microbiology, 2022)
Integrase strand transfer inhibitor (INSTI)-containing regimens in HIV-1-infected patients have experienced a global increase. Recently, WHO has emphasized the need to fast-track the transition to dolutegravir (DTG)-based antiretroviral (ARV) treatments. However, continued surveillance of INSTI resistance is recommended. In this study, clinical, epidemiological, and virological features associated with INSTI resistance diagnosed in Spain were analyzed. Samples collected between 2008 and 2021 from HIV-1-infected patients were analyzed in integrase, protease, and reverse transcriptase using Sanger population sequencing. ARV drug resistance was evaluated with the Stanford University HIVdb program. Among 2696 patients, 174 (6.5%) had INSTI resistance, all of them to first-generation INSTIs, and 71 (2.6%) had also resistance to second-generation INSTIs. Of these, only 5 individuals were exposed to DTG as the only INSTI, in whom resistance development was associated with poor treatment adherence and/or resistance to other ARV classes. Of newly HIV-1-diagnosed individuals, 0.92% carried INSTI-resistant viruses, with low prevalences maintained along time and only one had low-resistance to DTG. Persons who inject drugs, age over 39 years, resistance to other ARV classes, and longer time from diagnosis were associated with INSTI resistance (p<0.001). Non-subtype B INSTI-resistant viruses lacked the Q148H+G140S resistance pathway and showed lower INSTI resistance levels than subtype B viruses. In conclusion, INSTI resistance is uncommon and associated with long-term infections, older age and additional resistance to other ARV drug classes, and is rare in newly HIV-1 infections. Our results also support the preferential use of DTG-containing regimens in first-line treatments, although surveillance of INSTI resistance is encouraged.